Peningkatan Kapasitas Kepala Desa untuk Memajukan Desa melalui BUMDES di Jawa Timur - Oyong Lisa; Djuni Farhan; Sugeng Mulyono (Universitas Muhammadiyah Malang, 2024)
Purpose – Badan Usaha Milik Desa (BUMDes) is one of the crucial instruments in advancing villages and enhancing community welfare. The success of BUMDes greatly depends on the capacity of the village head in leading and managing BUMDes. The community service activities aim to enhance the capacity of village heads in the East Java Province to manage BUMDes. Design/methodology/approach – The community service activities are conducted through training and mentoring methods for Village Heads in the East Java Province. Findings – The Village Head, after participating in training and mentoring activities, experienced a significant increase in knowledge and skills in managing BUMDes. This improvement encompasses managerial aspects, planning, and the implementation of BUMDes programs. This indicates that the community service activities conducted effectively enhanced the capacity of the Village Head, which in turn has the potential to advance the overall welfare of the village community. Originality/value – The originality of these community service activities lies in the holistic, integrated, and contextually adapted approach in enhancing the capacity of Village Heads and advancing BUMDes in the East Java Province.